Concurrent Infection with Dengue and Malaria: An Unusual Presentation - Mohsin Bin Mushtaq; Mehmood I. Qadri; Aaliya Rashid (Case Reports in Medicine)
Dengue and malaria are both endemic in South Asia and represent a major public health burden in this region. Though there have been some case reports of concurrent infection with dengue and malaria, yet there are only few cases of such infections reported from South Asia. Here, we present a case of a young male returning from a dengue endemic area who tested positive for the virus along with Plasmodium vivax and Plasmodium falciparum. In view of the severity of coinfection (Epelboin et al., 2012), overlapping symptoms, and a challenging obscurity of diagnosis, a multidimensional diagnostic approach is suggested.